On the impact of urban heat island and global warming on the power demand and electricity consumption of buildings—A review - Santamouris, M.; Cartalis, C.; Synnefa, A.; Kolokotsa, D. (Energy and buildings, 2015)
•We examine the impact of high ambient temperatures in electricity demand.•The increase of the peak electricity demand is analyzed.•The impact of ambient temperature increase in Europe is surveyed. Urban heat island and global warming increase significantly the ambient temperature. Higher temperatures have a serious impact on the electricity consumption of the building sector increasing considerably the peak and the total electricity demand. The present paper aims to collect, analyze and present in a comparative way existing studies investigating the impact of ambient temperature increase on electricity consumption. Analysis of eleven studies dealing with the impact of the ambient temperature on the peak electricity demand showed that for each degree of temperature increase, the increase of the peak electricity load varies between 0.45% and 4.6%. This corresponds to an additional electricity penalty of about 21 (±10.4)W per degree of temperature increase and per person. In parallel, analysis of fifteen studies examining the impact of ambient temperature on the total electricity consumption, showed that the actual increase of the electricity demand per degree of temperature increase varies between 0.5% and 8.5%.